Enhancement of nano-RC switching delay due to the resistance blow-up in ingaas - Ismail, Razali; Tan, Michael L. P.; Saad, Ismail (World Scientific Publishing, Singapore, 2007)
RC and transit-time delays in a nanocircuit, where the resistor is a few nanometers in length, are evaluated taking into account the velocity and current saturation and applied to RC switching delay in InGaAs heterojunction field effect transistor (HFET). Transit time delay is the dominant factor in the ohmic regime where the applied voltage V is less than the critical voltage V-c for the onset of nonlinear nonohmic behavior. However, RC time constant is predominant in the nonohmic regime and increases linearly with the applied step voltage. The power in the nanocircuit is smaller and rises linearly in the nonohmic regime as compared to the quadratic behavior in the ohmic regime.